Characterisation of Skin Biomechanical Properties via Experiment-Numerical Integration - Fazli Adull Manan, Nor; Muhamad, Linasuriani; Adam Mohd Adnan, Zurri; Azman Yahaya, Mohd; Mahmud, Jamaluddin (International Journal of Engineering and Technology, 2018)
By having specific mechanical properties of skin, computational program and analysis become more reliable by showing the real skin behaviour. Up to date, mechanical properties of biological soft tissues (skin) havenâ€™t been accepted solely for official usage. Therefore, characterisation of the skin biomechanical properties might contribute a new knowledge to the engineering and medical sciences societies. This paper highlights the success in characterising the hyperelastic parameters of leporine (rabbit) skin via experimental-numerical integration. A set of five sample of leporine skin were stretched using the conventional tensile test machine to generate the load-displacement graphs. Based on the Ogdenâ€™s constitutive equation and Mooney-Rivlin hyperelastic model, a stress-stretch equation was developed and a programme was written using Matlab. By varying the Ogdenâ€™s and Mooney-Rivlinâ€™s parameters, the programme was capable of plotting stress-stretch and load-displacement graphs. The graphs that best match the experimental results will constitut to the corresponding coefficient, Âµ, and Î± for Ogden Model and C1 and C2 material parameter for Mooney-Rivlin Model that will best describe the behaviour of the leporine skin. The current results show that the Ogdenâ€™s coefficient and exponent for the subject was estimated to be (Î¼ = 0.048MPa, Î± = 7.073) & (Î¼ = 0.020MPa, Î± = 9.249) for Anterior-Posterior (AP) and Dorsal-Ventral (DV) respectively for Ogden Model. Meanwhile the value for Mooney-Rivlin Model were estimated to be (C1 = 1.271, C2 = 1.868) & (C1 = 1.128, C2 = 1.537) for AP and DV respectively, which is in close agreement to results found by other researchers. Further analyses for comparison could be carried out by developing mathematical model based on other constitutive equation such as Arruda-Boyce and Neo-Hookean. Nevertheless, this study has contributed to the knowledge about skin behaviour and the results are useful for references.Â Â